Regular Physical Activities Inhibit Risk Factors of the Common Cold Among Chinese Adults - Tu, Renjie; Lu, Yifan; Tao, Kuan (Frontiers in Psychology, 2022)
Background: Physical activity (PA) has a significant health impact worldwide and has been linked to a lower risk of the common cold. Objective: To estimate the form of physical activity among Chinese adults, and the correlation between physical activity and number of the common cold in China’s eastern, central and western areas. Design: a cross-sectional study. Setting: China’s eastern, central, and western regions from November 30th, 2020, to March 30th, 2021. Patients: 1920 healthy participants, aged over 18 years old, with internet access. Then collected self-reported physical activity behaviors and number of the common cold. Measurements: The authors calculated preference, intensity, frequency, and duration of physical activity in Chinese based on gender, age, and broad occupational categories and explored the potential effect between these factors and the common cold. Results: Approximately 20.4% of participants reported not participating in sports regularly. Except for gender, there were significant differences in PA preference and intensity among the remaining individuals (p<0.05). Sixteen common exercises were divided into three intensity levels by Borg-CR10-Scale: low (5), moderate (8), and high-intensity exercises (3), and the corresponding intensity, frequency, and duration were computed with significant differences (p<0.05). The most popular workouts are “Brisk walking” and “Running”. Age, sex, and occupation had no significant effect on colds (p>0.05). However, Intensity shows a U-shaped dose-response relationship with colds, whereas the frequency and duration have an inverse dose-response relationship (p<0.05). High intensity combined with high frequency increased colds the most. Nevertheless, non-exercise groups always have the most colds in each comparison. Limitations: The result may be vulnerable to recall bias. Conclusion: Intensity showed U-shape, frequency, and duration showed inverse response to the number of colds last year, but age, sex, and occupation had no significant effects. High intensity and high frequency mixed increased colds the most, regardless of duration.